Diagnóstico Ambiental De La Calidad De Agua Del Rìo Chimbadero De La Ciudad De Tena Mediante El Análisis Físico, Químico Y Microbiológico, Para Proponer Un Plan De Manejo Ambiental - Guanga Merino, Javier Vinicio (2016)
TENA is a city of continuous growth urban and tourist, but unfortunately currently them rivers are being contaminated, the river Chimbadero not is an exception, this is is located in an area critical because its proximity to the camal municipal and to the project of stuffed health, has an impact circumstantial in the quality of its waters, the research consisted in establish five points of sampling , physical, microbiological, and chemical analysis according to annex I of the unified text of environmental legislation (TULAS). Is carried out 112 surveys, for a population of 2,331, the 71% expressed that the stuffed health and the Camal cause pollution to the river Chimbadero, of the analysis of field and laboratory physical, chemical, in them five points of sampling of water, determined that is found low them limits permissible according to the standard Ecuadorian TULAS, while for the analysis microbiological that correspond to coliform fecal and total the limit is of 10000UFC / 100 ml , laboratory results determined a value of 3600000UFC / 100ml, which indicates that they are about the limits of standard Tulas in five water sampling points, is due to the presence of the landfill and the Municipal slaughterhouse whose Leachates are discharged into the River, proposed and environmental management Plan as a tool to mitigate preserve , protect, recover and control the impacts produced by the different activities caused by the man in the river Chimbadero,